The relationship between body condition score and backfat in gestating sows - M G Young; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
Backfat and body condition score were measured on 731 sows in a commercial swine facility to assess the accuracy of feeding sows in gestation based on body condition score. Body condition score was poorly correlated (r2 = 0.19) with backfat thickness. For example, sows assessed with a body condition of 3 ranged in backfat from 0.3 to 0.9 in. (7.5 to 23 mm). This illustrates the need to find a more objective method of measuring body condition (such as ultrasound) in order to properly adjust feeding levels and thus reduce variation in backfat of sows.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Sows; Backfat; Body condition score